Big Data Modeling Based on KNN-RF-SVM and Its Application in Product Sales Forecasting Field - Zhang, Chen; Ren, Hongru; Lu, Xiuhua; Yuan, Qunyao; Lu, Renquan (2022 International Conference on Intelligent Manufacturing and Industrial Big Data (ICIMIBD), 2022)
For the past few years, the big data prediction model has been extensively applied to our life. How to boost the performance of the big data prediction model has become a critical issue to be solved. At present, most of the big data prediction models are used single algorithm model. In this paper, K-nearest neighbor (KNN) algorithm, random forest (RF) algorithm and support vector machine (SVM) algorithm are used as the basic classifier, and the algorithm is combined through soft voting to obtain the KNN-RF-SVM combination model. Through the experiment test, the results indicate that the KNN-RF-SVM combined model is all the better than the single algorithm model in accuracy, precision, recall rate and F1 score.